LEGAL PROTECTION OF AI-ASSISTED SCIENTIFIC WORK ORIGINALITY IN THE DIGITAL SOCIETY - Muhammad Fachri; Marlin; Ahmad Syahird; Fahmi Afham Fuady (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The rapid development of artificial intelligence (AI) technology presents new challenges for the legal system, particularly in the enforcement of copyright over scientific works produced with the assistance of Chat Generative Pre-Trained Transformer (ChatGPT). This study aims to analyze the aspects of originality and legal protection of AI-assisted scientific works by employing a normative legal research method with statutory and conceptual approaches. The findings show that, under Law No. 28 of 2014 on Copyright, only natural persons or legal entities may be recognized as authors. ChatGPT cannot be regarded as a legal subject because it lacks consciousness and juridical responsibility, and functions merely as a technical tool under human control. Legal protection for scientific works generated with AI assistance can only be granted where there is a demonstrable human contribution in the form of creative input, supervision, and meaningful intervention in the process of creation. In the context of community service, this research highlights the importance of enhancing digital legal literacy among academics so that AI can be utilized ethically, lawfully, and responsibly. Thus, law functions not only as a regulatory instrument, but also as an educational and protective tool in shaping a just digital society that upholds academic integrity.